Dialogi pisarzy młodopolskich z "Lillą Wenedą" Juliusza Słowackiego - Rusek, Iwona E. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
This article analyses connections between the romantic idea of spiritual development and modernist search for the truth of existence. The patron of activities directed in this way was Juliusz Słowacki, whose works and life inscribed in artistic-philosophical actions of modernist artists and the text which most fully expressed the analysed issues was the drama entitled “Lilla Weneda”. Modernist writers, for whom the problems of the strength of the character, the will, inner transformation or lack of it, initiated a dialogue with the tragedy by "Balladyna"’s author in their texts (W. Berent “Próchno”, M. Wolska “Swanta”, A. Lange “Wenedzi”, J.A. Kisielewski “Sonata”). This dialogue took place along several lines (fate, symbolism of a ritual, the figure of a priestess, mysterious objects, the figure of the Bride, the idea of wedding, the desire to be reborn). The present analysis has indicated strong semantic-symbolic connections between the text by Juliusz Słowacki and his modernist ‘interlocutors’.
Modernist writers’ dialogues with “Lilla Weneda” by Juliusz Słowacki
Keywords: Słowacki Juliusz; "Lilla Weneda"; Młoda Polska; historia recepcji